2016
DOI: 10.3945/jn.115.221267
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Supplementation Enhances Fetal Growth and Protein Synthesis in Rats with Intrauterine Growth Restriction

Abstract: l-Citrulline increases fetal growth in a model of IUGR, and the effect may be mediated by enhanced fetal muscle protein synthesis and/or increased NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 82 publications
2
32
1
1
Order By: Relevance
“…The lack of an anabolic effect of citrulline in the current study contrasts with the enhanced fetal growth observed with the antenatal maternal citrulline supplementation in our previous reports [20,21]. As citrulline may exert its effect through citrulline conversion to arginine, our finding also contrasts with the anabolic effect of postnatal arginine in neonatal piglets [28,29].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of an anabolic effect of citrulline in the current study contrasts with the enhanced fetal growth observed with the antenatal maternal citrulline supplementation in our previous reports [20,21]. As citrulline may exert its effect through citrulline conversion to arginine, our finding also contrasts with the anabolic effect of postnatal arginine in neonatal piglets [28,29].…”
Section: Discussioncontrasting
confidence: 99%
“…In recent studies, we found that oral citrulline supplementation during gestation enhanced fetal growth and protein anabolism in a model of intrauterine growth restriction (IUGR) induced by dietary protein restriction in pregnant rats [20,21]. To the best of our knowledge, whether postnatal citrulline supplementation impacts growth or glucose metabolism in IUGR is not known.…”
Section: Introductionmentioning
confidence: 99%
“…73,74 Other have found higher nitrite/nitrate concentrations in umbilical venous plasma 55 or an increase in endothelial nitric oxide synthase (eNOS) protein staining in placental vessels compared with normal pregnancies, suggesting that increased NO production could be a compensatory response to improve blood flow in the placenta. 75,76 Decreased NO synthesis, evaluated in terms of nitrate/nitrite production, was observed in animal models of IUGR induced by a reduction in utero placental perfusion pressure 77 or maternal LPD 78,79 and in a rat model of developmental programming of HTN induced by exposing pregnant rats to androgens. 80 Reduced NO bioavailability may result either from altered NO synthesis or from NO scavenging by other molecules, such as ROS.…”
Section: Impaired No Bioavailabilitymentioning
confidence: 99%
“…Osowska et al were first to demonstrate that supplementation of enteral feeding with citrulline improved nitrogen balance and increased muscle protein synthesis in rats that had undergone extensive small intestinal resection [19]. An anabolic effect of citrulline supplementation on muscle protein synthesis was documented in other experimental models of undernutrition in aged, malnourished rats [20], or rat fetuses with intrauterine growth restriction due to maternal undernutrition [21].…”
Section: Introductionmentioning
confidence: 99%